The comparison of discomfort level between upper arm and forearm tourniquet - Ng, E.S.; Ting, J.R.; Foo, S.L.; Akram, S.A.; Fadzlina, A.A.; Alwiyah, J.S.; Ahmad, Tunku Sara (Malaysian Medical Association, 2006)
The conventional upper arm tourniquet used for hand and wrist operations may cause significant discomfort to patient when the procedure is performed under local anaesthesia. Forearm tourniquet causes less muscle ischeamia and pain. The discomfort experienced while using a forearm and upper arm tourniquet was assessed in 96 healthy subjects. Tourniquet placed on both sides was inflated sequentially to 250mmhg for five minutes on different hand. The discomfort level was assessed using a small visual analogue scale and complications were recorded. In the upper arm tourniquet, 24.9% had mild, 60.5% had moderate and 14.6% had severe pain whereas with forearm tourniquet, 99% had mild pain and only 1% had moderate pain. Seventy-nine percent of the subjects tested with forearm tourniquet had no discomfort at all. The average discomfort level for upper arm and forearm tourniquet was 4.72 and 0.39 respectively, which is statistically significant. Complications that were observed only in upper arm tourniquet included prolonged tingling, burning sensation and discomfort and stiffness of the upper limb. We concluded that forearm tourniquet was safe and well tolerated and should be used more often when indicated.